Peningkatan Tata Kelola Usaha Keripik Pisang Sale Pada Kelompok Ibu-Ibu Pengrajin Di Bungus Teluk Kabung - Ezizwita Ezizwita; Tri Sukma; Enny Arita; Yofina Mulyati; Firsta Firsta (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
The smoked banana chips business "Karya Mandiri" is a business of independent craftsmen who produce smoked banana chips for sale at Bungus Teluk Kabung. This business has been established for 25 years, starting with the desire to take advantage of the availability of banana raw materials which are abundant and easily available around the business location, supported by the desire and ability to produce sale bananas. It turns out that the product is quite attractive to the market as evidenced by the large number of customers. In the development of this business, the owner realized the lack of ability in terms of business governance and marketing. This raises concerns for business owners. Based on these problems, it is necessary to develop business management capabilities for partners to develop their business. Partners need guidance in business management, both in terms of human resource management, production management, marketing management, and financial management. This service activity aims to improve entrepreneurial governance skills from aspects of business activities which include human resources, production processes, marketing systems and financial management, all of which are interrelated. The method used in this service is coaching and counseling for businesses that are partners, namely the home industry of banana chips sale "Karya Mandiri". The result of this community service program is that business people understand the importance of knowledge about business management to manage their business better and faster develop, understand the importance of qualified and capable human resources, dare to produce innovative and more diverse products, increase product marketing and aggressively carry out promotions by utilizing internet technology, for example through Facebook, Instagram, WhatsApp, and various other electronic media and be able to manage company finances well as well as being able to become an independent entrepreneur who is highly motivated in running his business, so it is hoped that the business being run can develop for the better.